2007
DOI: 10.1074/jbc.m611821200
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Occupancy and Channel-opening Kinetics

Abstract: AMPA glutamate ion channels are tetrameric receptors in which activation to form the open channel depends on the binding of possibly multiple glutamate molecules. However, it is unclear whether AMPA receptors bound with a different number of glutamate molecules (i.e. one being the minimal and four being the maximal number of glutamate molecules) open the channels with different kinetic constants. Using a laser pulse photolysis technique that provides microsecond time resolution, we investigated the channel-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 34 publications
9
27
0
Order By: Relevance
“…We favor, therefore, an interpretation of n = 2 as the minimal number of glutamate molecules bound to a receptor to open the channel. This conclusion was also consistent with the results from a study of an AMPA receptor mutant where k obs was collected up to saturation (34), and from studies of both AMPA and kainate receptor channels (17, 19, 22). Furthermore, as is known in kainate receptors, channel activation by activating only a subset of subunits, instead of all four, in a tetrameric complex can occur (35).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We favor, therefore, an interpretation of n = 2 as the minimal number of glutamate molecules bound to a receptor to open the channel. This conclusion was also consistent with the results from a study of an AMPA receptor mutant where k obs was collected up to saturation (34), and from studies of both AMPA and kainate receptor channels (17, 19, 22). Furthermore, as is known in kainate receptors, channel activation by activating only a subset of subunits, instead of all four, in a tetrameric complex can occur (35).…”
Section: Resultssupporting
confidence: 89%
“…To achieve a better estimate of n, K 1 and k op by nonlinear regression using eq 2, we decided to first fix the value of k cl so that we reduced one variable. This was possible because when L ≪ K 1 , eq 2 was reduced to k obs ≈ k cl , suggesting that (a) k obs at a low glutamate concentration would reflect k cl , and (b) the value of k cl was independent of whatever the n value might be as in eq 2 (22, 34). Based on this rationale, we identified k obs of 310 s −1 as k cl for the wild-type and mutant hGluK2 receptors.…”
Section: Resultsmentioning
confidence: 99%
“…5 in Sun et al, 2002). The former was confirmed by determining the rate of channel closure for GluR1 L497Y (Pei et al, 2007), whereas kinetic modeling of the same mutant suggested that both entry into the desensitized state and the rate of ligand dissociation were decreased relative to GluR1 WT (Mitchell and Fleck, 2007). Although this modeling study did not incorporate slower channel closure, it seems probable that a combination of these three factors blocks desensitization and slows deactivation in the AMPA receptor leucine to tyrosine mutants.…”
Section: Discussionmentioning
confidence: 76%
“…I max is the maximum current amplitude, and I t is the current amplitude at time t . Our previous studies of AMPA receptors, including a mutant AMPA receptor, for their channel-opening kinetic mechanisms led us to conclude that binding of two glutamate molecules per receptor (i.e., n = 2) was sufficient to open the channel (38). Using the laser-pulse photolysis technique, we previously determined the k op of (8.0 ± 0.49) × 10 4 s −1 and the k cl of (2.6 ± 0.20) × 10 3 s −1 , respectively, for the channel-opening kinetic constants of the GluA2Q flip receptor (21).…”
Section: Homologous Competitive Binding Assaymentioning
confidence: 99%